The Involvement of Women in Household Decision-Making Process in Myanglung Municipality - Shrestha, Lalit (Intellectual Journal of Academic Research, 2025)
In Nepal, traditional gender roles often place men in dominant positions within households, limiting women’s participation in household decision-making processes. Understanding women’s involvement and the factors influencing their role is crucial for promoting gender equity. This study aims to assess the extent of women’s participation in household decision-making in Myanglung Municipality, identify key factors affecting their involvement, and examine the implications for family dynamics. Primary quantitative data were collected from households in Myanglung Municipality, Tehrathum. Data analysis focused on identifying the level of women’s participation and the influence of variables such as age, caste, and education on decision-making power. Findings demonstrate that men predominantly control household decisions, especially those related to income. Women tend to participate more actively in decisions related to limited domains. Factors including age, caste, and educational attainment significantly affect the degree of women’s involvement in decision-making processes. There exists a significant gender gap in household decision-making in Myanglung Municipality. Increasing women’s participation requires addressing socio-cultural barriers and enhancing educational opportunities to foster a more equitable distribution of decision-making authority within households.